Soil chemical attributes and initial growth of corn crop by adding domestic and industrial sewage sludge (Bioscience Journal, 2017)
In recent decades, organic and/or inorganic nonconventional waste such as sewage sludge, agro-industrial or industrial waste, inorganic waste, steel slag, etc., have become some of the most promising alternatives to commercial fertilizer shortages or rising prices. Hence, the aim was to evaluate morphological changes in corn plants and variations in chemical properties of cohesive Yellow Latosol (Oxisol), after the incorporation of sewage sludge doses from domestic waste and the dairy industry. The experimental units were randomised blocks designed with four repetitions. The treatments consisted of five doses of each sewage sludge incorporated into the soil, that is: Domestic Sewage Sludge (DSS) in doses of 0.0; 3.1; 4.6; 6.1 and 9.2 Mg ha-1 (on a dry basis ), and Industrial Sewage Sludge (ISS) in doses of 0.0; 5.2; 7.8; 10.4 e 15.6 Mg ha-1 (on a dry basis), all equivalent to 0; 100; 150; 200 and 300 kg of total N ha-1. Doses equivalent to 150 - 300 kg total N ha-1 led to greater gains in stem diameter, number of leaves, fresh and dry mass of leaves. Increasing doses of both sewage sludges enable gains in the morphological variables studied, except for root length. Positive linear increments occur in the pH and phosphorus content of soils when the doses of sewage sludge are increased. The exchangeable aluminium and potential acidity are reduced, from the first dose of industrial sewage sludge, with no significant difference for domestic sewage sludge.